Preparation, structural property, and antioxidant activities of a novel pectin polysaccharide from the flowers of Hibiscus syriacus Linn. - Chen, Jialong; Ye, Chaojun; Zhang, Lu; Xie, Zhiliang; Zhu, Jianjun; Zhang, Zhi (Frontiers in Nutrition, 2025)
IntroductionOxidative stress, triggered by an imbalance between reactive oxygen species (ROS) production and cellular antioxidant defense mechanisms, is implicated in various pathological conditions. Plant-derived polysaccharides have gained significant attention as potential natural antioxidants due to their biocompatibility, biodegradability, and structural versatility.MethodsThis study focuses on the purification, structural characterization, and antioxidant activities of a novel pectin polysaccharide (HFPS) isolated from the flowers of Hibiscus syriacus Linn. HFPS was purified using anion-exchange chromatography. Its chemical composition, monosaccharide profile, molecular weight distribution, and structural properties were elucidated through various analytical techniques.ResultsHFPS exhibited a predominant acidic monosaccharide composition, with galacturonic acid as the major constituent, indicating its pectin nature. The free radical scavenging activity of HFPS against ABTS·, DPPḤ, and ·OH radicals was evaluated, demonstrating a positive correlation between its antioxidant capacity and concentration. Furthermore, HFPS effectively protected HepG2 cells against H2O2-induced oxidative stress by reducing ROS accumulation, modulating redox-related enzymes (Superoxide dismutase, Catalase, Glutathione peroxidase), and alleviating oxidative damage. Notably, HFPS upregulated the expression of antioxidant-related genes, including B-cell lymphoma-2 (Bcl-2), heme oxygenase 1 (HO-1), NAD(P)H quinone oxidoreductase 1 (NQO1), and nuclear factor erythroid 2-related factor 2 (Nrf2), while downregulating pro-apoptotic genes like Bcl-2-associated X protein (Bax) and Caspase-3. These findings suggest that HFPS exerts its antioxidant effects by modulating the Nrf2/HO-1 pathway and redox homeostasis.DiscussionThis study contributes to the understanding of the structure-function relationships and antioxidant mechanisms of HFPS, highlighting its potential applications as a natural antioxidant in various fields.